A cross sectional study on food safety knowledge among adult consumers - Ruby, Genevie Eleanor; Ungku Zainal Abidin, Ungku Fatimah; Lihan, Samuel; Jambari, Nuzul Noorahya; Radu, Son (Elsevier, 2019)
The purpose of this study was to assess the consumers' food safety knowledge and its determinants. The analysis was based on data collected through a cross-sectional survey in East Malaysia, which described the knowledge about personal hygiene, food borne disease symptoms, high-risk foods, cross-contamination, and temperature control held by Sibu-based consumers. Up to 99.5% of consumers correctly answered the question on hand hygiene in food handling. However, only 23.3% had a detailed knowledge of the temperature effect on bacterial growth in food. The level of food safety knowledge differed by gender, age, education level, number of children and food preparation frequency. The logistic regression model used for this data found a high level of food safety knowledge among tertiary graduates (OR = 42.26; 95% CI: 9.97, 179.06). It also highlighted the importance of food safety knowledge as an effort to control food borne diseases (FBD), by focusing on consumer food handling in the home and how to extent the benefits of food safety education to the whole society.